Model Pertumbuhan Tinggi dan Diameter Eucalyptus sp. - Suhartati, Tatik; Wahyudiono, Sugeng; Sari, Atika Kumala (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2024)
Growth models can provide information on how the tree grows with age, and can be used to predict the level of timber production. This study aims to find the growth model of height (H) and diameter (Dbh) and determine the maximum volume cycle of Eucalyptus sp. in PT. XYZ. Samples were taken in various compartments with ages of 18 months, 30 months 42 months and 54 months. The total sample of 64 plots was divided into 48 plots for model development and 16 plots for model validation. The four types of models analyzed were Linear, Logarithmic, Inverse and S models. Modeling was done through regression analysis. Model acceptance criteria were significant in F test, R2 value and SeR, while model validation criteria used RMSE, SR, SA and Bias values. The best growth model in this study for both Height and Dbh was the S model with the equations Height=e^(3.0355 - 1.3525/x) and DBH=e^(2.6491 - 1.2843/x). The maximum volume cycle was achieved at the age of 4.5 years with a volume of 172.7284 m3/ha and a Mean Annual Increament (MAI) value of 38.3841 m3/ha/year.